METAPHORICAL MEANING ATTACHED TO LIQUOR ADVERTISEMENTS - Harnats Ardhiansyah; Angelika Riyandari; Y.E. Budiyana (Soegijapranata Catholic University, 2003)
Advertising may be viewed as the construction of the semiotic worlds for persuading purchasers to consume what is advertised. Printed advertisement often involves manipulation of linguistic forms to achieve the persuasion. In addition. metaphor is an effective way to achieve the persuasion role since it is closely related to the way of people 's thinking and concept of something in their mind. which is fUndamentally metaphorical in nature. The data are collected from two liquor advertisements and respondents' questionnaires. The two advertisements discussed in this article were collected from Maxim magazine. September 2002 edition and the respondents' questionnaires were distributed to 20 respondents to find out their interpretations on metaphorical advertisements due to written language message of advertisements. In addition. the two examples of printed advertisements. instances of metaphorical advertisements. are reviewed. identified. and explained by using the theories of Saussure's Dydical Sign Model to find the process of metaphors attached to the advertisements. The results of the study show that people's interpretations on metaphors are basically related to their experience offered by metaphors. It means that people will interpret the meaning of the advertisements based on such circumstances in which they have ever been involved in.